Producing renewable electric energy through a microbial fuel cell in the rice field - HADI WISA NUGRAHA; GUNAWAN DJAJAKIRANA; SYAIFUL ANWAR; DWI ANDREAS SANTOSA (Society for Indonesian Biodiversity, 2020)
Abstract. Nugraha HW, Djajakirana G, Anwar S, Santosa DA. 2020. Producing renewable electric energy through a microbial fuel cell in the rice field. Biodiversitas 21: 4139-4146. Microbial Fuel Cell (MFC) is an alternative technology that converts chemical energy into electrical energy using microbes. This study aimed to apply MFC technology in the rice field to produce renewable electricity by utilizing microbes that have been previously isolated. The study was conducted in two experiments. The first experiment was carried out to select MFC prototypes with different in the oxygen circulation system (anode and cathode holes) that capable of producing the highest Voltage. The second experiment was performed to test the selected MFC prototype for electricity production in 12 combination treatments of microbes, organic matter, and fertilization (mixed NPK fertilizer) with three replications on rice cultivation in a greenhouse. The results showed that the best MFC prototype was a prototype that has two holes, each at anode and cathode (MFC 2). The highest electrical Voltage was generated by the treatment with microbes and organic matter, without fertilizer. The treatments produced the highest electrical current was the addition of microbes, organic matter, without and with 50% fertilizer. The highest power density was generated by the treatment with microbes and organic matter, without fertilization. The addition of ex-situ isolated microbes significantly increased the production of electricity.